2019
DOI: 10.3389/fnins.2019.00132
|View full text |Cite
|
Sign up to set email alerts
|

Music Intervention Approaches for Alzheimer’s Disease: A Review of the Literature

Abstract: Music interventions have been widely adopted as a potential non-pharmacological therapy for patients with Alzheimer’s disease (AD) to treat cognitive and/or behavioral symptoms of the disease. In spite of the prevalence of such therapies, evidence for their effectiveness report mixed results in the literature. The purpose of this narrative review is to investigate the effectiveness of various intervention strategies (music therapy vs. music listening techniques) and music type used in the intervention (individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 39 publications
3
95
1
5
Order By: Relevance
“…This form of therapy is also used in people with brain injury and neurodegenerative disorders [30,31]. Perhaps the common element here is that musical interventions improve inhibitory control which in turn improves behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This form of therapy is also used in people with brain injury and neurodegenerative disorders [30,31]. Perhaps the common element here is that musical interventions improve inhibitory control which in turn improves behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, these authors addressed different aspects of verbal memory with and without music, with verbal material from their childhood associated with a music, that is, words that had always been associated with a melody or cantinela. As say Leggieri et al 3 music listening may act as a relaxation technique and therefore provide a long-term impact for the patient.…”
Section: Introductionmentioning
confidence: 94%
“…In spite of the prevalence of such therapies, evidence for their effectiveness report mixed results in the literature. 3 In this line, Prickett and Moore 4 showed that patients with Alzheimer's can be stimulated through songs that are familiar to them and with constant practice they can even learn new songs, despite not being able to remember recent conversations. In their study, these authors addressed different aspects of verbal memory with and without music, with verbal material from their childhood associated with a music, that is, words that had always been associated with a melody or cantinela.…”
Section: Introductionmentioning
confidence: 99%
“…Music listening has the advantage that it does not rely on a trained music therapist. Two recent reviews have looked at the difference between active music therapy and music listening (Leggieri et al, 2019;Tsoi et al, 2018). Both found that music listening could be effective, but it was important that music was individualised.…”
Section: Er7: Using Music To Provide Comfort and Reassurancementioning
confidence: 99%
“…Both found that music listening could be effective, but it was important that music was individualised. Familiar music may have more positive effects on people with dementia because it can invoke autobiographical memories (Leggieri et al, 2019). A few studies have looked at the use of MP3 players to provide individualised music but this can be costly and requires support from staff or volunteers (Murphy et al, 2018;Hebert et al, 2018).…”
Section: Er7: Using Music To Provide Comfort and Reassurancementioning
confidence: 99%